Agenesis of internal carotid artery associated with isolated growth hormone deficiency: a case report and literature review. Issue 1 (December 2015) - Stagi, Stefano; Traficante, Giovanna; Lapi, Elisabetta; Pantaleo, Marilena; Becciani, Sabrina; Mortilla, Marzia; Seminara, Salvatore; de Martino, Maurizio
Abstract Background Agenesis of the internal carotid artery (ICA) is a rare congenital abnormality, sporadically reported to be associated with a combined congenital hypopituitarism. Nevertheless, only a few cases have been extensively described, and none of these have been characterized by an isolated growth hormone (GH) deficiency. Case presentation Here, we describe a 17-year old boy referred to our hospital for fatigue, decreased muscle strength and severe headache reported after the cessation of rhGH treatment for a GH deficiency diagnosed at the age of 2 years and 3 months. Magnetic resonance imaging (MRI) showed an adenohypophyseal hypoplasia with a lack of posterior pituitary hyperintensity, whereas MRI angiography indicated the absence of a normal flow void in the left ICA. Endocrinological tests confirmed the GH deficiency (GH peak after growth-hormone-releasing hormone (GHRH) + arginine: 2.42 ng/mL) with a very low IGF-I value (31 ng/mL) and normal function of other pituitary axes. Conclusion To the best of our knowledge this is the first confirmed case of an isolated GH deficiency in a patient with ICA agenesis. The presence of an isolated pituitary deficit is unlike to be considered only as an effect of hemodynamic mechanism, suggesting a role for genetic factor(s) as a common cause of these two rare birth defects. Further studies could clarify this issue and the underlying mechanisms to better understand the etiopathogenetic characteristics of this disorder.